Pelatihan Positive Self-talk untuk Meningkatkan Kepercayaan Diri pada Mahasiswa - Annisa Furqon Iriyanti; Dian Kinayung (Universitas Ahmad Dahlan, 2021)
Positive Self-talk Training to Increase Self Confidence of StudentsNew students are oftentimes required to able adapting to new environments and become more creative, and also independent. This makes some students feel a lack of confidence in their capabilities. This study aimed to determine the effect of positive self-talk training to increase self-confidence in students. The research method used is a quasi-experimental quantitative method with a pretest-posttest control group design. The subjects in this research were 14 people of Yogyakarta universities with a semester range from the first semester until the third semester. Subjects were divided into two groups, experimental group, and control group. Data analysis was used Wilcoxon and Mann-Whitney U tests. Wilcoxon tests, the results obtained were p=0.027 and z=-2.207, meaning that there was a significant difference in self-confidence assessment before and after treatment. Meanwhile, Mann Whitney U test resulted in p=0.014 and z=-2.464, meaning that there was a significant difference in self-confidence scores between the experimental group and the control group.